Assessment of a bicycle helmet liner with semispherical cones. (February 2016) - Teng, Tso-Liang; Liang, Cho-Chung; Nguyen, Van-Hai
Helmets reduce the frequency and severity of head and brain injuries resulting from bicycle crashes. Generally, a bike helmet consists of the outer shell, liner, vents and straps. The liner is the major helmet component reducing head injury in an accident. Using superior energy absorbing structures and materials as helmet liners to meet the higher safety standards should thus be considered. In this study, a shock absorption test was performed in accordance with the EN1078 standard to evaluate the energy absorption capability of a helmet on the market. Then, the finite element analyses of helmet impact tests modelled using LS-DYNA software. To verify the accuracy of the model, the simulation results were compared with experimental data. Finally, an innovative design of helmet model with semispherical cone liner was considered in this study. To assess the dynamic energy absorption of this helmet, a simulation was performed in accordance with the EN1087 standard for shock absorption tests. The resultant simulation revealed that the helmet with the semispherical cone liner has the potential to protect the human head. This innovative design for a helmet liner can serve as a valuable idea to assist future development of safety-helmet technologies.